Designing Online Module-Based English Learning Materials for STAIN Bengkalis's First-Year Students - Rini Fitria (Akademika: Jurnal Keagamaan dan Pendidikan, 2021)
The goals of this study were to create appropriate online module-based English learning materials for STAIN Bengkalis's First-Year Students in order to provide them with diverse English knowledge and to learn about the First-Year Students' reactions to the module design. This research was research and development (R&D). The module's participants were STAIN Bengkalis first-year students from three different majors (N=50), with the sample drawn using a random sampling technique. In this study, questionnaires and observation sheets were used as instruments. The needs analysis questionnaire was used to gather information about the students' needs, and the try-out questionnaire was used to gather information about the students' agreement with the module. The collected data were analyzed both qualitatively and quantitatively. This research has resulted in a set of applicable online module-based English materials for First-Year Students. The product came with eight menus. They are the Exercises, Grammar Focus, and Useful Information menus, as well as the Useful Vocabulary, Reading, Listening, Writing, and Speaking menus. All of the activities or tasks were created with the students' needs and preferences in mind. With the indication of students' try-out questionnaire means ranging from 3.2 to 3.55 (4 points Likert Scale) in terms of content, module component, and design, the product was deemed applicable and appropriate. This result demonstrates that students respond positively to the designed online module-based English materials.